Hubungan Antara Siswi Yang Memiliki Indeks Massa Tubuh (IMT) Overweight Dengan Depresi Di MAN 1 Surakarta - Listianto, Arif Kurniawan, dr. Rh. Budhi Muljanto, Sp. KJ, dr. Dodik Nursanto (2015)
Background : The excessive increased of Body Mass Index (BMI) may caused negative feeling of body image and self-esteem especially among adolescent girls. This is caused by adolescent girls tend to have an awareness about her body shape than adolescent boys. Negative body shape perception because of by excessive of BMI contributed to depression. Objective : To informed the relationship between female students who have an overweight body mass index (BMI) with depression at MAN 1 Surakarta. Method : An observational analytic with cross sectional design applied on 70 female students at MAN 1 Surakarta. Responden selected with purposive sampling method then retrieved data in the form of z-score and BDI. Data was analized by Mann-Whitney test with SPSS 17.0 for windows. Result : The result of the study shows p=0,000 (p<0,05) which the mean of BDI score in overweight female students was 11,03 and the mean of normal weight female students or control group was 7,17. Conclusion : There was signifficant relationship between female students who have a overweight body mass index with depression at MAN 1 Surakarta which female students with overweight have a higher depression score than female students with normal weight. Recommendation : A continuous control was needed to know the difference score of depression on the alteration of weight.